Aptamer-mediated Plasmodium-specific diagnosis of malaria - Cheung, Yee-Wai; Dirkzwager, Roderick M.; Wong, Wai-Chung; Cardoso, Josiane; D'Arc Neves Costa, Joana; Tanner, Julian A. (Biochimie, 2018)
There is a critical need for better malaria rapid diagnostic tests to discriminate Plasmodium falciparum and Plasmodium vivax infection given the recent observation of HRP2 deletions in P. falciparum parasites. We previously identified a DNA aptamer, 2008s, that targets P. falciparum lactate dehydrogenase (PfLDH) and developed a sensitive aptamer-tethered enzyme capture (APTEC) assay. Here, we characterise two different LDH-binding DNA aptamers in their species-specific activities, then integrate within biochemical diagnostic assays and test in clinical samples. An enzyme-linked oligonucleotide assay demonstrated that aptamer pL1 bound with high affinity to both PfLDH and P. vivax lactate dehydrogenase (PvLDH), whereas aptamer 2008s was specific to PfLDH. An aptamer-tethered enzyme capture (APTEC) assay confirmed the specificity of 2008s in binding and capturing the enzyme activity of PfLDH which could be observed colorimetrically. In malaria patient samples, the 2008s APTEC assay was specific for P. falciparum blood samples and could discriminate against P. vivax blood samples. An aptamer for specific detection of falciparum malaria holds promise as a new strategy for species-specific malaria diagnosis rather than the conventional HRP2 immuno-assay. •An aptamer-based falciparum malaria specific detection strategy is described.•The specificities of two LDH-binding DNA aptamers were characterised.•Species-specific malaria detection assay is validated using clinical whole blood samples.